Evaluation Yield of Sunflower (Farrokh cultivar) under Effects of Conventional Deficit Irrigation and Partial Root Zone Drying - A. Rezaei Estakhroeih; S. Khoshghadam; M. Ebrahimi Serizi; A. Badiehneshin (مجله آب و خاک, 2015)
Water shortage is the most important factors on crop production in the world. Several methods of deficit irrigation are solutions for reduction of irrigation water. To understand the effects of conventional deficit irrigation and partial root zone drying treatments on yield, yield components and water use efficiency of sunflower (Farrokh cultivar), one study was carried out. The research was conducted on Shahid Bahonar University of Kerman in the spring of 2011. A factorial experiment in a randomized complete block design with one control (full irrigation) and 18 deficit irrigation treatments in three replications was considered. Deficit irrigation treatments were: conventional deficit irrigation (irrigation with %80, %60 and %40 ETP) and partial root zone drying (irrigation with %80, %60 and %40 ETP). Every deficit irrigation treatment was conducted in three growth stage of sunflower (all periods of growth, vegetative growth stage and reproductive growth stage).The results showed that the conventional deficit irrigation treatments (irrigation with 80% ETP) in vegetative growth had the highest plant height, leaf area, leaf area index and head diameter. Also, the maximum biological yield equal to49054, maximum grain yield is equal to 9934/3 and maximum oil yield is equal to 2441/2 kg per hectare in the conventional deficit irrigation treatments (irrigation with 80% ETP) in vegetative growth occurred.The highest water use efficiency for grain yield is equal to 1/46,forbiological yield equal to7/21 and for dry forage yield is equal 5/7 kilograms per cubic meter of water. According to results,conventional deficit irrigation (irrigation with %80, %60 and %40 ETP) is recommended on based.